2021
DOI: 10.1038/s41591-020-1126-7
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue is associated with cardiometabolic health

Abstract: White fat stores excess energy, whereas brown and beige fat are thermogenic and dissipate energy as heat. Thermogenic adipose tissues markedly improve glucose and lipid homeostasis in mouse models, although the extent to which brown adipose tissue (BAT) influences metabolic and cardiovascular disease in humans is unclear 1,2 . Here we retrospectively categorized 134,529 18 F-fluorodeoxyglucose positron emission tomography-computed tomography scans from 52,487 patients, by presence or absence of BAT, and used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
348
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 458 publications
(411 citation statements)
references
References 41 publications
11
348
0
3
Order By: Relevance
“…BAT was originally thought to have evolved as a compensatory defense system against hypothermia in mammals [9,26]. By increasing energy expenditure, the activation of BAT also functions to improve whole-body glucose homeostasis and plays a critical role in mitigating the deleterious effects of obesity and diabetes [27][28][29]. Accumulating evidence suggests that NPs not only stimulate lipolysis by binding to the receptor NPR-A and subsequently activating the cGMP-PKG pathway but also activate BAT via the further upregulation of UCP1 [9,14,19].…”
Section: Discussionmentioning
confidence: 99%
“…BAT was originally thought to have evolved as a compensatory defense system against hypothermia in mammals [9,26]. By increasing energy expenditure, the activation of BAT also functions to improve whole-body glucose homeostasis and plays a critical role in mitigating the deleterious effects of obesity and diabetes [27][28][29]. Accumulating evidence suggests that NPs not only stimulate lipolysis by binding to the receptor NPR-A and subsequently activating the cGMP-PKG pathway but also activate BAT via the further upregulation of UCP1 [9,14,19].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical research, Richard and his group’s data obtained from the follow-up investigation of 443 patients indicated that the activity of BAT had a negative relationship with vascular inflammation and CVD ( 60 ). And the beneficial effects of BAT on improving blood glucose, TG and HDL play an significant role in promoting cadiometabolic health ( 61 ). The next question for the researchers is how BAT is involved into the occurrence and development of CVD.…”
Section: Bat and Cardiovascular Diseasesmentioning
confidence: 99%
“…Several pathological processes associated with obesity may inhibit proper differentiation of brown fat, among them genetics, inflammation and OxS [29]. Although BAT appearance and correct function have been proven to be connected with reduced risk of obesity, type 2 diabetes, or CVD for several years, and animal studies have shown a link between BAT and improved glucose and lipid balance [30,31], their connection with mood regulation seems a new research target [32]. It has been shown that appearance and higher activity of BAT protects against stress-induced obesity and diabetes in mice and lower pre-stress activation of brown adipocytes is connected rather with the vulnerability to this phenomenon [33].…”
Section: Etiopathologic Features In Commonmentioning
confidence: 99%